Millet production, challenges, and opportunities in the Asia-pacific region: a comprehensive review - Harish, M. S.; Bhuker, Axay; Chauhan, Bhagirath Singh (Frontiers in Sustainable Food Systems, 2024)
Global warming, water scarcity, population growth, rising food prices, urbanization, and other socio-economic factors pose significant threats to agriculture and food security in the 21 st century. This situation is particularly grave for low-income individuals in the Asia-Pacific region. To tackle this challenge and eradicate hunger and poverty, it is imperative for scientists to explore alternative food sources, covering all stages from production through processing to consumption.Cereal grains serve as a crucial food source and hold substantial importance in human diets. Therefore, revamping the food system becomes crucial to achieve food and nutritional security. A pragmatic approach towards reaching this goal involves ensuring universal access to affordable, wholesome, and nourishing food through the utilization of milletsnutrient-dense grains (often referred to as Nutri-cereals) that offer a rich array of vital macronutrients, micronutrients, carbohydrates, protein, dietary fiber, lipids, and phytochemicals.Leveraging these grains holds the potential to significantly alleviate the challenges of food insecurity and malnutrition.Millet, a drought-resistant grain, constitutes a primary source of carbohydrates and proteins for populations residing in semi-arid regions of Africa and Asia.Given its crucial contribution to national food security and potential health advantages, there is a growing focus among food scientists. Additionally, the United Nations designated 2023 as the International Year of Millet, underscoring its importance.This article delves into various methods of production and processing, highlighting opportunities to enhance the production and nutritional qualities of millet. We attribute millets to inadequate rainfall distribution, poor crop management high prices of farm inputs such as fertilizer and pesticides and low adoption of improved varieties by the farmers.It also outlines the constraints, challenges, and future prospects associated with promoting millet as a viable food source for the burgeoning population. Despite the promise that millets hold, they have not received adequate research attention. Therefore, increased research efforts on integrating genomics in genome-wide markertrait association are imperative, encompassing germplasm collection, protection, evaluation, consumption patterns, development of high-yielding cultivars, processing techniques, and policy interventions. Such initiatives are necessary to bolster the cultivation of millets and harness their potential to address the escalating global food challenge.